Analisis Kebutuhan Modul Ajar untuk Memfasilitasi Kecakapan Komunikasi dan Representasi Matematis di Era Merdeka Belajar - Afriliziana, Linda Ardani; Roza, Yenita; Maimunah, Maimunah (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
The purpose of this study was to determine the need for developing tools for teaching (modul ajar) that can facilitate students' communication skills and mathematical representation in phase D of data analysis and probability content in the era of independent learning. Data collection techniques were carried out by interview teacher who teaches mathematics in class VII and giving tests to assess students' communication skills and mathematical representations. The object of this research is tools for teaching that facilitate students' communication skills and mathematical representation in the era of independent learning. The subjects in this study were 23 students of class VIII junior high school in one of the junior high schools in Pekanbaru City and four math teachers of class VII junior high school in Pekanbaru City. The used data collection are curriculum analysis, material analysis, and student analysis. Based on the results of the analysis, information was obtained that the teacher had difficulties in making tools for teaching due to the lack of examples of tools for teaching that could be used as a guide and the students' communication skills and mathematical representation were low at 45.48% so that students needed a tools for teaching that could facilitate communication skills and mathematical representation especially on data analysis and probability content.